Luis Vélez de Guevara y la comedia palatina - Miguel Zugasti (Criticón, 2017)
From a global viewpoint of Vélez de Guevara’s theater, this article selects eight works belonging to the genre of the palace play. Of the eight plays six are of certain authorship (Amor es naturaleza, Celos, amor y venganza, La obligación a las mujeres, El rey en su imaginación, El rey muerto and Virtudes vencen señales) and two are of doubtful attribution (El embuste acreditado y disparate creído and Cumplir dos obligaciones y duquesa de Sajonia). Each work is analyzed in terms of twelve characteristic features that define the palace play, and then the study concludes with a division of the corpus into two groups: comical palace plays (five titles) and serious palace plays (three titles).